Evaluating Environmental and Public Health Hazards of Urban Flooding: Clinical Consequences and Considerations - Umaru, Isaac John; Asare, Solomon Ossom; Umogbai, Debora Akinola; Olayemi, Abimbola Gbenga; Chukwudi, Emmanuel Eluu (Darul Yasin Al Sys, 2026)
Urban flooding poses a significant threat to environmental integrity and public health, particularly in rapidly expanding regions of Nigeria. This study evaluates the environmental contamination, clinical consequences, and psychosocial impacts of urban flooding across six districts—Gwarinpa, Lokogoma, and Lugbe in Abuja, and Yola North, Demsa, and Numan in Adamawa State—selected for their history of seasonal flooding, population density, and strategic urban importance. A mixed-methods approach was employed, combining environmental sampling, clinical data collection, and household surveys. Water and soil samples were analyzed for microbial contamination (E. coli), pH, turbidity, and heavy metals (lead, mercury, cadmium) in line with WHO standards, while clinical data from health facilities were used to assess the prevalence of flood-related illnesses, including diarrhea, skin infections, and respiratory symptoms. Mental health outcomes were evaluated through structured surveys administered to 300 residents, focusing on anxiety and post-traumatic stress disorder (PTSD). Results revealed elevated levels of E. coli and heavy metals in flood-affected zones, with Lokogoma and Yola North recording the highest contamination, and these districts also reporting the highest incidence of waterborne diseases and respiratory conditions. Mental health symptoms were prevalent across all districts, with more than 50% of respondents in Lokogoma and Demsa reporting signs of anxiety and PTSD, while healthcare facilities in Lugbe and Numan experienced disruptions in chronic disease management and medication access, underscoring systemic vulnerabilities. In conclusion, urban flooding in Abuja and Adamawa has profound environmental and public health implications, and the findings highlight the need for integrated flood management strategies, including infrastructure upgrades, environmental monitoring, healthcare system strengthening, and mental health integration. Tailored interventions across these districts are essential to mitigate future risks and build community resilience in the face of climate-induced disasters.